Work performance of extension agents: skills of transfer of technology and human resource development in cocoa industry - Mohd Pakri, Murni Azureen; Hassan, Salim; Olagunju, Oluwatoyin; Abd Samad, Mohd Yusoff; Kasin, Ramle (Universiti Putra Malaysia Press, 2022)
Transfer of technology (ToT) and human resource development (HRD) are essential components to acknowledge extension agents’ performance. Understanding the foundations and implications of ToT and HRD is vital for improving agriculture extension agents in research and extension programmes. This study was designed to determine extension agents’ ToT and HRD skills to explain the work performance of Malaysian Cocoa Board (MCB) extension agents in East Malaysia. A total of 315 productive cocoa farmers exposed to the extension activities for a minimum of five years and had attended two basic training from the agency were selected to answer the questionnaire within a month. The researcher applied Krejie and Morgan formula to determine the sample size based on the population using stratified random sampling. The data were analysed using descriptive statistics, multiple regression and Pearson correlation analysis. Results showed a positive and moderate relationship between ToT and HRD towards work performance. However, from the six variables tested, only three variables were significant towards work performance, namely technical skill (p=0.000), leadership skill (p=0.015) and decision-making skill (p=0.000). Therefore, the extension agents’ skills must be strengthened, their working knowledge updated, and new concepts for developing agriculture that can fulfil complicated demand patterns, reduce poverty and pressure and increase productivity must be developed. This study also strengthens the iceberg model by adding six characteristics of skills in extension agents. The outcomes would contribute to the policymakers and MCB’s management in elevating the extension agents’ performance through training and developing ToT and HRD.